PENGARUH INVESTASI, PENDIDIKAN, UPAH MINIMUM, DAN TEKNOLOGI TERHADAP KESEMPATAN KERJA DI KABUPATEN/KOTA PROVINSI BALI: PENGARUH INVESTASI, PENDIDIKAN, UPAH MINIMUM, DAN TEKNOLOGI TERHADAP KESEMPATAN KERJA DI KABUPATEN/KOTA PROVINSI BALI - Ni Luh Eka Widiasari, Ni Luh Eka Widiasari; Ida Ayu Meisthya Pratiwi (Universitas Udayana, 2025)
Bali Province is a famous tourist destination for foreign visitors, but its development process remains inefficient, particularly due to inadequate employment opportunities which hinder economic growth. This study aims to analyze the partial and simultaneous effects of investment, education, minimum wages, and technology on employment opportunities across regencies/cities in Bali Province during the period 2015–2023. The results reveal that employment opportunities are significantly and simultaneously influenced by investment, education, minimum wages, and technology. However, in partial terms, employment opportunities are positively affected by education and minimum wages, while investment and technology do not show significant individual effects. These findings imply the need for targeted policies to reduce inequality in employment through educational improvements, wage policy adjustments, and equitable digital access. Effective collaboration among the government, private sector, and civil society is essential for inclusive employment growth in Bali’s local economies.